THE RECOVERY OF PERFORMANCE CHARACTERISTICS OF STRUCTURES TRANSPORT CONSTRUCTIONS - Rudenko, D. V. (Science and Transport Progress, 2009)
The basic groups of factors affecting negatively the of concrete structure in transport structures and decreasing their longevity are determined in the article. They are the destruction of basic construction materials, the extreme loadings and influence on constructions of the structures, as well as operational violations. In real conditions these factors are in interaction, which is casual and indefinite in character. In this context the interaction of some factors